Strategi Pemanfaatan Nanas Lokal Melalui Diversifikasi Sirup dalam Pemberdayaan UMKM di Desa Tanjung Baru - Epriyani, Jihan; Chaisarani, Fadia; Putri, Melia Sari Onika; Utami, Sherly Adithia Putri; Anugra, Defri; Setiawan, Budi; Meirisari, Vhika (Abdimas Universal, 2025)
Most farmers in Tanjung Baru Village sell pineapples directly without processing, leading to suboptimal economic value. To address this issue, training is essential to enhance the added value of processed pineapple products. This community service initiative aims to improve the utilization of local pineapples in Tanjung Baru Village, Lembak Subdistrict, Muara Enim Regency, while also empowering farmers and MSME actors through product diversification. It consists of four stages: first, conducting surveys in pineapple farms and problem analysis to identify the potential and challenges faced by farmers and MSME actors; second, interviewing farm owners and MSME actors to gather information on farm management, production processes, and challenges; third, focusing on socialization regarding the processing of pineapples into value-added products such as pineapple syrup, along with entrepreneurial education on packaging techniques and basic financial calculations; and finally, emphasizing product packaging education by providing training on selecting appropriate packaging types, designs, and materials to ensure product quality, safety, and market appeal. The expected outcomes of this community service are to enhance the knowledge of farmers and MSME actors, improve product processing and packaging, and boost the local economy through the production of value-added pineapple syrup.